Overcoming The Dilemma Of Using Translation Within An Efl Classroom: التّغلب على معضلة استخدام التّرجمة داخل فصل دراسي للغة الإنجليزيّة كلغة أجنبيّة - Bensafa, Abdelkader (Maalim, 2022)
ELT or English Language Teaching is considered a multidisciplinary domain. In other words, the study of ELT draws its principles with other disciplines including: psychology, sociology, technology, ethnography, educational psychology, applied linguistics, and translation. Most of the problems are related to the use of the mother tongue (L1) in an ELT course where the core of the process is the language used by both teachers and students. In addition to this, the use of French as a prerequisite contributes in the dilemma of the usefulness as to the limitations of using translation in an ELT class. The aim of this paper is to shed light on the issues mentioned. Besides, it will try to find solution to overcome the problematic situation regarding when, where, and how to make the shift to translation (be it to L1 or French), when teaching English in particular, of great value.